Tularemia Outbreak among the Population of Khanty-Mansiisk and the Khanty-Mansiisk Region, Occurred in 2013 - N. A. Ostapenko; M. G. Solov’Eva; A. A. Kazachinin; I. I. Kozlova; N. M. Faizullina; E. B. Ezhlova (Проблемы особо опасных инфекций, 2015)
Natural tularemia foci in the territory of the Khanty-Mansiisk Autonomous District - Yugra are still active and sustainable ones despite of the extended periods of epidemiological welfare. Agent reservoir is the water vole. However, recently tularemia agent has been detected in the northern red-backed vole and common red-toothed shrew. Khanty-Mansiisk town, Berezovsky, Khanty-Mansiisk, Kondinsky, and Oktyabr’sky Regions are situated in the territory of the most active foci. Serious outbreaks of infection among the population occur with an interval up to 30 years. Their transmissibility preconditions the scale and intensiveness. All cohorts are under the risk of exposure, irrespective of the age and occupation, including the infants. The paper discusses tularemia outbreak impact on the population of Khanty-Mansiisk and the Khanty-Mansiisk Region in July-October, 2013. Casualty toll is 1005 cases. Given is a brief retrospective analysis of epidemiological situation on tularemia since 1930-s up to the onset of the outbreak under investigation. Described is the experience in management of the response activities.